Dimensions of Creativity in Secondary School High-Ability Students - Núria Arís Redó; María Ángeles Millán Gutiérrez; José-Diego Vargas Cano (MDPI AG, 2021)
The objective of this study was to analyze the dimensions of creativity in high-ability teenage students. Firstly, we reviewed the most relevant scientific contributions on creativity. Next, the dimensions of creativity in secondary school students who were previously identified as high-ability students were analyzed. The sample was obtained from 215 students, of which 31 were identified as high-ability students. The abilities associated with divergent thinking were assessed using the Torrance Test of Creative Thinking The fluency, flexibility, and originality dimensions were assessed with the Scientific-Creative Thinking Test. This study was conducted using a quantitative approach. Tests were administered during school hours from March to June 2019. They were corrected considering the protocols established by the original authors themselves. Data were analyzed using SPSS, version 24.0. The results provide evidence that high-ability students achieve higher scores in both the figurative-creativity and scientific-creativity dimensions. A significant relationship between creativity and high ability was therefore established. Students with high abilities and qualities require the educational support necessary to develop their talent. This study was of an exploratory nature and the results obtained contribute to developing future studies applying its findings in teenagers' teaching-learning process.